Improving Student Confidence With Electronic Health Record Order Entry - Sarkar, Arindam (PRiMER, 2021)
INTRODUCTION: Despite near-universal utilization of electronic health records (EHRs) by physicians in practice, medical students in most ambulatory settings gain limited experience with placing EHR orders. In this study, an individual preceptor site investigated the usefulness of a targeted curriculum in improving students’ EHR confidence and clinical reasoning skills. METHODS: Family medicine clerkship students assigned to one community health center were invited to participate in this prospective, survey-based study. In their first week, students observed a preceptor performing EHR tasks. For the remainder of the 4-week clerkship, students utilized decision support tools, assigned a working diagnosis, entered unsigned orders in the EHR, proposed an assessment, and discussed a plan with a preceptor. Students completed weekly questionnaires to self-report confidence across several EHR domains while preceptors synchronously evaluated students’ accuracy with entering orders correctly. RESULTS: From February 2017 to March 2020, all 49 eligible students completed the study. One hundred percent of students reported that placing EHR orders was beneficial to their medical education. The difference over time in learner confidence with placing EHR orders was statistically significant across every domain (eg, writing prescriptions, ordering labs and imaging). Preceptors’ evaluations of students’ accuracy with placing orders also showed significant improvement between each week. CONCLUSION: Clerkship-wide EHR training may be limited by multiple sites with multiple EHR products. This pilot study suggests that committed faculty at an individual preceptor site can offer a targeted curriculum to help students develop EHR confidence. We propose other preceptors similarly offer students this opportunity to maximize clerkship education.